Efficacy of novel osteotomy techniques in the treatment of congenital radial head dislocation - Miao, Wusheng; Li, Bo; Li, Junjun; Zhang, Kun; Zhang, Xiaobo (Frontiers in Pediatrics, 2026)
ObjectiveTo evaluate the clinical curative effect and imaging results of osteotomy and rotation surgery for congenital radial head dislocation.MethodsA retrospective analysis was conducted on 20 children with congenital radial head dislocation who underwent clinical surgical treatment meeting the inclusion criteria from June 2,015 to June 2024 via osteotomy and rotation surgery. The sex, age, and follow-up time of the children were recorded. Clinical efficacy was assessed through elbow joint range of motion (pronation, supination, flexion), and imaging results were evaluated via the Nakamura grading system, while related complications such as wound infection and neuronal injury were recorded.ResultsAll surgeries were completed, with 14 males and 6 females aged 3–15 years, with an average age of 7.05 ± 3.98 years, and a follow-up time of 12–120 months, with an average of 33.95 ± 37.65 months. X-ray images of the elbow joint revealed that the humeroradial joint was reduced, with no recurrence of radial head dislocation, no nonunion at the osteotomy site, and no developmental abnormalities of the proximal ulna. The preoperative elbow joint pronation angle was 81.15° ± 3.65°, supination angle was 83.15° ± 3.70°, and flexion angle was 129.80° ± 4.56°; the postoperative elbow joint pronation angle was 80.30° ± 4.44°, supination angle was 84.75° ± 3.24°, and flexion angle was 138.25° ± 3.46°. Among them, the hyperextension state of one child with elbow hyperextension disappeared after surgery. The range of motion of the elbow joint improved significantly. Nakamura grading revealed that 85.0% (17/20) of the children were excellent, and 15.0% (3/20) were good. No wound infections or neuronal injuries occurred in any of the children after surgery.ConclusionProximal ulnar osteotomy and rotation surgery is an effective treatment method for congenital radial head dislocation, demonstrating significant clinical efficacy and safety.